2016
DOI: 10.5057/ijae.ijae-d-16-00003
|View full text |Cite
|
Sign up to set email alerts
|

Appearance of Gold, Silver and Copper Colors of Glossy Object Surface

Abstract: Abstract:We investigated categorical regions and appearances of gold, silver and copper color, and glossiness for CG spheres with various chromaticities, lightnesses, and contrast glosses. It was found that the chromaticity regions of brown and yellow changed into gold color, those of gray and black into silver color, and a part of brown region changed into copper color with increase of contrast gloss. The magnitude estimates of gold, silver and copper color increased in high saturation chromaticity regions, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 26 publications
1
13
0
Order By: Relevance
“…These values were determined by referring to the report in Ref. . The luminance of copper color was lower than that of other metallic colors because of the color gamut limit of the projector and the light absorption characteristics of material samples.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…These values were determined by referring to the report in Ref. . The luminance of copper color was lower than that of other metallic colors because of the color gamut limit of the projector and the light absorption characteristics of material samples.…”
Section: Methodsmentioning
confidence: 99%
“…These chrominance values were selected from the copper color area reported in Ref. 10. The experimental stimuli were prepared at 100 cd/m 2 intervals with a luminance greater than 100 cd/m 2 .…”
Section: Experimental Stimulimentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, the correlation between the perception and appearance of metallic colors, such as gold and silver, is unexpectedly still under study and has been of interest in recent decades [1][2][3][4][5][6][7][8]. For instance, Okajima et al reported the importance of luminance distribution for metallic recognition [1].…”
Section: Introductionmentioning
confidence: 99%
“…For instance, Okajima et al reported the importance of luminance distribution for metallic recognition [1]. In addition to this, several factors for metallic recognition have been reported such as the specular/diffuse ratio [2,3], lighting condition [4,5], surface irregularity [6], shape recognition [7], observation area [8], etc. Although these research studies certainly indicate that the recognition of metallic colors is different from common colors, the prescribed method and index for quantification of metallic image based on perception is not defined, presumably due to the difficulties from said multidimensional recognition factors.…”
Section: Introductionmentioning
confidence: 99%